Thermal noise variance of a receive radiofrequency coil as a respiratory motion sensor - Andreychenko, A.; Raaijmakers, A.J.E.; Sbrizzi, A.; Crijns, S.P.M.; Lagendijk, J.J.W.; Luijten, P.R.; van den Berg, C.A.T. (Magnetic resonance in medicine, 2017)
Purpose Development of a passive respiratory motion sensor based on the noise variance of the receive coil array. Methods Respiratory motion alters the body resistance. The noise variance of an RF coil depends on the body resistance and, thus, is also modulated by respiration. For the noise variance monitoring, the noise samples were acquired without and with MR signal excitation on clinical 1.5/3 T MR scanners. The performance of the noise sensor was compared with the respiratory bellow and with the diaphragm displacement visible on MR images. Several breathing patterns were tested. Results The noise variance demonstrated a periodic, temporal modulation that was synchronized with the respiratory bellow signal. The modulation depth of the noise variance resulting from the respiration varied between the channels of the array and depended on the channel's location with respect to the body. The noise sensor combined with MR acquisition was able to detect the respiratory motion for every k‐space read‐out line. Conclusion Within clinical MR systems, the respiratory motion can be detected by the noise in receive array. The noise sensor does not require careful positioning unlike the bellow, any additional hardware, and/or MR acquisition. Magn Reson Med 77:221–228, 2017. © 2016 Wiley Periodicals, Inc.